The Role of Social Media-Based Project-Based Learning Model in Increasing Community Participation in the Process of Forming Environmental Regulations - Lanawaang, Janeman Jehezkiel; Mesra, Romi (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To examine the role of Social Media-Based Project-Based Learning in increasing community participation in the process of forming Environmental Regulations, integrating digital technology with civic education and public policy formation. Methodology: The study employed a qualitative approach using a literature review method. Data was collected from academic databases using relevant keywords. Thematic analysis was used to identify key themes. Data source triangulation and peer debriefing were implemented to ensure validity and reliability. The analysis considered socio-political and cultural factors influencing implementation. Main Findings: The Social Media-Based PBL model showed significant potential in increasing public participation in Environmental Regulation formation. It improved understanding of environmental issues and the legislative process, expanded information accessibility, and enhanced the quality of community input. However, challenges like the digital divide and misinformation spread were identified. Novelty/Originality of this study: This study uniquely integrates Project-Based Learning, social media use, and Environmental Regulation formation processes. It offers a new perspective on increasing community participation through active learning and digital technology, potentially transforming public policy formation to be more inclusive and responsive to community and environmental needs.